2022
DOI: 10.1039/d2nr05291a
|View full text |Cite
|
Sign up to set email alerts
|

Insights into mechanisms of diphosphine-mediated controlled surface construction on Au nanoclusters

Abstract: Unraveling the rules governing the size regulation of nanoclusters is of great importance not only in fundamental research, but also in practical applications because of the high structure-property correlation in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 76 publications
(93 reference statements)
0
15
0
Order By: Relevance
“…Of note, the UV-vis spectra of the formed Au clusters in this study is distinct from the reported one (+2 vs. 0). Besides, the Au 21 cluster co-protected by SCy and dppp ligands was not reported, 30 and the etching of Au 23 with Au I dppp generates Au 22 cluster exclusively in the early study. Herein, using Au 6 as a dppp-donating reagent, the Au 21 cluster co-protected by SCy and dppp ligand was gained as a main product.…”
Section: Inset)mentioning
confidence: 99%
See 2 more Smart Citations
“…Of note, the UV-vis spectra of the formed Au clusters in this study is distinct from the reported one (+2 vs. 0). Besides, the Au 21 cluster co-protected by SCy and dppp ligands was not reported, 30 and the etching of Au 23 with Au I dppp generates Au 22 cluster exclusively in the early study. Herein, using Au 6 as a dppp-donating reagent, the Au 21 cluster co-protected by SCy and dppp ligand was gained as a main product.…”
Section: Inset)mentioning
confidence: 99%
“…The addition of different thiolate ligands (TBBzT/TBBT/2-NPT) results in the size-growth of Au 23 to Au 24 /Au 25 /Au 28 , 27,28 while the addition of phosphine ligand results in a distinct size-reduction of Au 23 → Au 22 (ref. 29 and 30)/Au 21 . 30 Meanwhile, the addition of MSCy (M = Ag/Au) complexes results in the formation of heavily Ag-doped alloy (AuAg) 25 31 and Au 28 , 32 respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reactivities of metal nanoclusters are fundamental in analyzing structural evolution, tailoring physicochemical properties, and promoting practical applications. Specifically, owing to their high reactivities, cluster-based functional nanomaterials have mutable and regulatable characteristics since nanocluster templates are easily modified with external conditions (acting as transforming driving forces), such as ligand exchange, [39][40][41][42] metal exchange, [43][44][45] redox, [46][47][48][49][50] and photo/temperature/pH variation [51][52][53] (Scheme 1). Accordingly, several cluster-based functional nanomaterials with unique features (such as enhanced stability, high sensitivity, or fast dynamic response) have been prepared for practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study reports the successful introduction of diphosphine ligands onto the cluster surface by adding Au–diphosphine complexes to a thiolate-protected Au NC, [Au 23 (SR) 16 ] − . 27 Motivated by this successful example, we adopted a similar strategy with Ag NCs. In this work, PPh 3 ligands have been introduced into the NCs successfully together with a dopant.…”
mentioning
confidence: 99%